Properties of fire-retardant vermiculite-concrete composite and fine-grained concrete for two-layer reinforced cement structures - T. A. Khezhev; G. N. Khadzhishalapov; F. M. Shogenova; A. Kh. Artabaev; M. Kh. Mashukova (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. Development of compositions of fire-retardant vermiculite-concrete composites for reinforced cement structures. Investigation of the properties of fire-retardant vermiculite-concrete composite and fine-grained concrete for two-layer reinforced cement structures.Method. Methods for increasing the fire resistance of reinforced concrete structures are considered. Research is focused on the development of fire-retardant composites using expanded vermiculite and volcanic ash. To improve the physical and mechanical properties of the fire-retardant composite, a mixture of Portland cement, gypsum, lime, basalt fiber, saponified wood resin, volcanic ash and expanded vermiculite has been developed. For the study of vermiculite concretes reinforced with basalt fiber, a second-order rotatable plan of the regular hexagon type was used.Result. Fiber-vermiculite concretes are proposed, which have improved fire-retardant properties compared to known compositions. This is due to the better preservation of the fiber-vermiculite-concrete layer when heated as a result of fiber reinforcement. Also, thanks to the addition of SDO, the fire-retardant properties of the composite increase due to the additional porosity of the fiber-vermiculite-concrete. The parameters of the "stress-strain" diagram of a vermiculite-concrete composite and fine-grained concrete have been obtained.Conclusion. Vermiculite concretes with an average density of 480-560 kg/m3 have the best fire-retardant properties. The developed two-layer reinforced cement structures have high fire resistance.